Sweep : The Story of a Girl and Her Monster - Auxier, Jonathan (New York : Amulet Books, 2018)
In nineteenth-century England, after her father's disappearance Nan Sparrow, ten, works as a "climbing boy," aiding chimney sweeps, but when her most treasured possessions end up in a fireplace, she unwittingly creates a golem.
Includes bibliographical references.
Keywords: Orphans -- Juvenile fiction; Chimney sweeps -- Juvenile fiction; Golem -- Juvenile fiction; Homeless persons -- Juvenile fiction; Friendship -- Juvenile fiction; Orphans -- Fiction; Chimney sweeps -- Fiction; Golem -- Fiction; Homeless persons -- Fiction; Friendship -- Fiction; Fantasy; JUVENILE FICTION / Family / Orphans & Foster Homes; JUVENILE FICTION / Social Issues / Homelessness & Poverty; JUVENILE FICTION / Fantasy & Magic; Great Britain -- Juvenile fiction -- History -- 19th century; London (England) -- Juvenile fiction; Great Britain -- Fiction -- History -- 19th century; London (England) -- Fiction; Fantasy fiction